Optimization of formulation and drying temperature of dried Cassava Getuk with black mulberry (Morus Nigra L.) juice using response surface method (RSM) - Taufik, Yusman; Sutrisno, Asep Dedy; Widiantara, Tantan; Apsari, Feby Dwi; Hariadi, Hari (Edelweiss Applied Science and Technology, 2025)
The purpose of this research is to develop an optimal formulation for producing dried cassava getuk infused with black mulberry juice, utilizing the Design Expert version 13 software and the Response Surface Methodology (RSM). The study evaluates both chemical and organoleptic responses. Chemical responses include moisture content and total carbohydrate content, while organoleptic responses assess color, aroma, taste, and texture. Based on the predictions generated by the Design Expert software, the optimal formulation comprises 65% cassava, 10% black mulberry juice, and a drying temperature of 70°C. The predicted outcomes for this formulation are a moisture content of 27.294%, a total carbohydrate content of 84.033%, and organoleptic scores of 4.00 for aroma, 4.74 for color, 3.59 for taste, and 3.95 for texture. The model’s accuracy, indicated by the validation value, is 0.886, demonstrating a high level of reliability in the predicted results.